Bias in case - Control studies: Can it be avoided? - Fernanda de Oliveira Souza; Samilly Silva Miranda; Alessandra Laís Pinho Valente; Tânia Maria de Araújo; Jenny Rose Smolen (Universidade de Santa Cruz do Sul, 2016)
Backgraund and objectives:Although case control studies have numerous advantages, they are vulnerable to biases that can mask the true results of the study and therefore should be interpreted with caution.The objective of this article is to critically approach, through a literature review, the biases that can affect this type of study design and the possible strategies to overcome those biases.Contents:The most well-known biases, present in the delineation of case control studies, were those related to selection and measurement. Conclusion: However, although this type of study is subject to possible errors, preventative measures put in place during the planning of case control studies and even during and after its execution can help guarantee scientific rigor.This review of the literature can serve as an important instrument for the development and interpretation of case-control studies.